MENGOPTIMALKAN KEAKTIFAN DAN PRESTASI BELAJAR MELALUI DISKUSI KELOMPOK MATA PELAJARAN EKONOMI KELAS XI-10 SMAN 6 KEDIRI - Sari, Happy Desiana; Arifin, Zainal; Rose Mita Lukiani, Eunike (Universitas Nusantara PGRI Kediri, 2024)
This research focuses on improving students' activity and learning achievement in class XI-10 at SMAN 6 Kediri by using group discussion methods in economics subject. Using a classroom action learning approach, the method was specifically designed to improve student engagement and learning outcomes. The results showed significant progress: student engagement increased from 61.75% in Cycle I to 76.47% in Cycle II, while learning achievement increased from 85% to 88.23%. The group discussion method proved to be more effective than the traditional methods commonly used. This research's novelty lies in applying this method, which effectively improved students' activity and learning achievement in class XI-10 SMA Negeri 6 Kediri, providing a better solution to the school's learning problem.